2010
DOI: 10.1158/1535-7163.mct-10-0550
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Constitutive Activation of STAT3 by Curcurbitacin-I (JSI-124) Sensitized Human B-Leukemia Cells to Apoptosis

Abstract: Phosphorylation of STAT3 on serine 727 regulates gene expression and is found to be elevated in many Bleukemia cells including chronic lymphocytic leukemia (CLL). It is, however, unclear whether targeting STAT3 will be an effective antileukemia therapy. In this study, we assessed in vitro antileukemia activity of the STAT3 inhibitor JSI-124 (cucurbitacin I). JSI-124 potently induces apoptosis in 3 B-leukemia cell lines (BJAB, I-83, and NALM-6) and in primary CLL cells and was associated with a reduction in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 44 publications
(55 reference statements)
6
44
0
Order By: Relevance
“…Previous reports have shown that cucurbitacin I suppresses STAT3 activation in other cancer cell lines, such as breast cancer (24) and leukemia cells (25). In the present study, we determined the effect of cucurbitacin I on STAT3 in colon cancer cells.…”
Section: Cucurbitacin I Suppresses Colon Cancer Cell Proliferation Mmentioning
confidence: 82%
“…Previous reports have shown that cucurbitacin I suppresses STAT3 activation in other cancer cell lines, such as breast cancer (24) and leukemia cells (25). In the present study, we determined the effect of cucurbitacin I on STAT3 in colon cancer cells.…”
Section: Cucurbitacin I Suppresses Colon Cancer Cell Proliferation Mmentioning
confidence: 82%
“…Nevertheless, among natural inhibitors, curcumin was shown to inhibit phosphorylation of STAT3 at both tyr705 and ser727 residues in biliary cancer cells (Prakobwong et al 2011). Interestingly, the inhibition of ser727 phosphorylation has been shown to induce apoptosis in Human B-leukemia and other cell lines constitutively expressing phosphorylated STAT3 in ser727 by curcubitacin-I (JSI-124) (Ishdorj et al 2010). Obviously, B-leukemia cells are known to express activated STAT3 with constitutive phosphorylation in ser727 but not in tyr705, supporting the role of ser727 phosphorylation in the oncogenic activity of STAT3 and suggesting this residue as a potential target for natural inhibitors of STAT3 activity.…”
Section: Resultsmentioning
confidence: 99%
“…[43][44][45][46][47] Several lines of evidence have indicated that cucurbitacin-I promotes cell cycle arrest and/or apoptosis in glioma, 48,49 lung, 42,50 breast, 51 and other malignancies. [52][53][54][55] Previously we observed that blockade of the JAK/STAT pathway by cucurbitacin-I enhanced the efficacy of SRC family kinase (SFK) inhibition with dasatinib in glioma cells. 48 Chumbalkar et al performed a tyrosine-directed search for signaling events downstream of DEGFR (EGFRviii) and identified STAT5 phosphorylation at Y699 as a key event.…”
Section: Introductionmentioning
confidence: 99%